2019
DOI: 10.31744/einstein_journal/2019rb4898
|View full text |Cite
|
Sign up to set email alerts
|

Isolated branched-chain amino acid intake and muscle protein synthesis in humans: a biochemical review

Abstract: Alongside a proper diet, ergogenic aids with potential direct and/or indirect physical performance enhancing effects are sought after for improved adaptation to physical training. Nutritional ergogenics include diet composition changes and/or dietary supplementation. Branched-chain amino acids valine, leucine and isoleucine are widely popular among products with ergogenic claims. Their major marketing appeal derives from allegations that branched-chain amino acids intake combined with resistance physical exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…In the present study, nutritional status, including BCAA metabolism, may have been at baseline without any immediate influence in the athletes and the controls who did not exercise, eat meals or BCAA supplements for 12 h before sample collection. However, another study found that resistance physical exercise prolongs muscle protein synthesis stimulation approximately 24 h post-workout [32]. An assessment of the relationship between amino acid imbalances and skeletal muscle mass in athletes under a longer period than 24 h without exercise before sample collections will prove the validity of the present results.…”
Section: Discussionsupporting
confidence: 49%
“…In the present study, nutritional status, including BCAA metabolism, may have been at baseline without any immediate influence in the athletes and the controls who did not exercise, eat meals or BCAA supplements for 12 h before sample collection. However, another study found that resistance physical exercise prolongs muscle protein synthesis stimulation approximately 24 h post-workout [32]. An assessment of the relationship between amino acid imbalances and skeletal muscle mass in athletes under a longer period than 24 h without exercise before sample collections will prove the validity of the present results.…”
Section: Discussionsupporting
confidence: 49%
“…At this time, supplementing branched-chain amino acids can save muscle glycogen, make the energy source of skeletal muscle to last, and increase muscle endurance. 99 , 100 …”
Section: The Potential Role Of Gut Microbiota In Gut-muscle Axismentioning
confidence: 99%
“…One of the main pathway by which the loss of muscle mass contributes to the appearance or the progression of other diseases is the alteration of protein turnover and metabolism in the skeletal muscle tissue [9,10]. In addition, other factors such as the reduced anabolic response to protein feeding during aging [11,12], contributes to the loss of muscle mass in individuals with sarcopenia. Confirming this, metabolic studies showed that older individuals aged 65 years and over require approximately 2% more protein intake per meal to maximize muscle protein synthesis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Most randomized placebo controlled trials (RCTs) have included interventions using whey protein as a supplement, because these contain large amounts of leucine (approximately 13 g leucine/100 g protein [13]). However, scientific evidence regarding the effect of leucine alone in sarcopenia is very scarce [11,[14][15][16]. We performed an RCT in order to ascertain whether the administration of leucine alone is effective in the treatment of sarcopenia and respiratory muscle function in older institutionalized individuals, a subgroup of older individuals with huge amount of comorbidity who are seldom evaluated in RCTs using leucine supplementation.…”
Section: Introductionmentioning
confidence: 99%